Na+/K+-ATPase as a Target of Cardiac Glycosides for the Treatment of SARS-CoV-2 Infection - Kauê Francisco Corrêa Souza e Souza; Kauê Francisco Corrêa Souza e Souza; Bianca Portugal Tavares Moraes; Bianca Portugal Tavares Moraes; Izabel Christina Nunes de Palmer Paixão; Izabel Christina Nunes de Palmer Paixão; Izabel Christina Nunes de Palmer Paixão; Patrícia Burth; Patrícia Burth; Adriana Ribeiro Silva; Adriana Ribeiro Silva; Cassiano Felippe Gonçalves-; et al. (Frontiers Media S.A., 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), identified for the first time in Wuhan, China, causes coronavirus disease 2019 (COVID-19), which moved from epidemic status to becoming a pandemic. Since its discovery in December 2019, there have been countless cases of mortality and morbidity due to this virus. Several compounds such as chloroquine, hydroxychloroquine, lopinavir-ritonavir, and remdesivir have been tested as potential therapies; however, no effective treatment is currently recommended by regulatory agencies. Some studies on respiratory non-enveloped viruses such as adenoviruses and rhinovirus and some respiratory enveloped viruses including human respiratory syncytial viruses, influenza A, parainfluenza, SARS-CoV, and SARS-CoV-2 have shown the antiviral activity of cardiac glycosides, correlating their effect with Na+/K+-ATPase (NKA) modulation. Cardiac glycosides are secondary metabolites used to treat patients with cardiac insufficiency because they are the most potent inotropic agents. The effects of cardiac glycosides on NKA are dependent on cell type, exposure time, and drug concentration. They may also cause blockage of Na+ and K+ ionic transport or trigger signaling pathways. The antiviral activity of cardiac glycosides is related to cell signaling activation through NKA inhibition. Nuclear factor kappa B (NFκB) seems to be an essential transcription factor for SARS-CoV-2 infection. NFκB inhibition by cardiac glycosides interferes directly with SARS-CoV-2 yield and inflammatory cytokine production. Interestingly, the antiviral effect of cardiac glycosides is associated with tyrosine kinase (Src) activation, and NFκB appears to be regulated by Src. Src is one of the main signaling targets of the NKA α-subunit, modulating other signaling factors that may also impair viral infection. These data suggest that Src-NFκB signaling modulated by NKA plays a crucial role in the inhibition of SARS-CoV-2 infection. Herein, we discuss the antiviral effects of cardiac glycosides on different respiratory viruses, SARS-CoV-2 pathology, cell signaling pathways, and NKA as a possible molecular target for the treatment of COVID-19.